Study on chemopreventive effects of raw and roasted β-glucan-rich waxy winter barley using an in vitro human colon digestion model. Issue 3 (16th March 2020) - Schlörmann, W.; Atanasov, J.; Lorkowski, S.; Dawczynski, C.; Glei, M.
Abstract : Fermentation supernatants of barley flakes exhibit chemopreventive effects in LT97 colon adenoma cells without impact of roasting. Abstract : Due to their unique dietary fibre composition, in particular β-glucan, the consumption of barley may contribute to a healthy diet and the prevention of colon cancer. The aim of the present study was to analyse chemopreventive effects of barley flakes obtained from a β-glucan-rich barley cultivar. In order to address the impact of heat treatment on potential chemopreventive effects, barley flakes were roasted (160 °C–180 °C, approx. 20 min). The flakes were subjected to in vitro digestion and fermentation. Fermentation supernatants (FS) were analysed for the concentrations of short-chain fatty acids (SCFA) and ammonia. Chemopreventive endpoints (growth inhibition, apoptosis, DNA integrity, gene expression of detoxifying enzymes) were analysed in LT97 colon adenoma cells. Concentrations of SCFA were increased in barley FS (2.5-fold, on average) with a shift of molar ratios towards butyrate production, while ammonia levels were significantly decreased (0.7-fold, on average) compared to the fermentation control. The growth of LT97 cells was significantly reduced by barley FS in a time- and dose-dependent manner, and caspase-3 activity of treated cells was significantly enhanced (up to 6.3-fold, on average). On average, treatment of cells resulted in increased mRNA levels of CAT (2.1-fold), SOD2 (2.2-fold) and GSTP1 (3.9-fold), while expression of GPx1 (0.3-fold) was significantly decreased in some cases. The roasting process did not cause genotoxic effects of barley FS and had no impact on chemopreventive properties. Our results indicate chemopreventive potential of in vitro fermented waxy winter barley, mediated primarily by growth inhibitory and apoptotic effects, which is largely unaffected by roasting.